NEW PARADIGM OF ART EDUCATION MANAGEMENT IN COLLEGES AND UNIVERSITIES UNDER LIAONING PROVINCE IN THE NEXT DECADE - Guoguang, Qiu; Chaisirithanya, Kamolmal; Chinatangkul, Chuanchom (วารสารวิจัยธรรมศึกษา, 2024)
The objectives of this research were: (1) to propose new paradigm of art education management in colleges and universities under Liaoning Province in the next decade ; and (2) to develop future wheel of implication for new paradigm of art education management in Colleges and Universities under Liaoning Province in the Next Decade. The research methodology was qualitative research with Delphi technique. The key informants were 20 experts in art education management. The data from three rounds of interviews were coded and classified by Delphi technology and future wheel research. The instrument used for data collection were open ended interview form and five-point rating scale questionnaire. Statistics is used for data analysis were adopt mode, median, Inter Quartile Range and content analysis was employed. The research findings revealed that: (1) the new paradigm of art education management in Colleges and Universities under Liaoning Province in the next decade is consisted of nine dimensions: the globalization of art education management, diversification (diversified development mode), education information management in art education, the concept of art education, teaching management in art education, organization management in art education, resource management in art education, quality management in art education, art education leadership；and (2) the future wheel of implication for new paradigm of art education management in Colleges and Universities under Liaoning Province in the next decade, based on the results of data analysis. The researcher used data analysis to get 87 consensus items and created an image of future wheels.